The problem of modelling of testing of abrasive wear in area of forming of powder materials - Moravec, J.; Bohušová, Z. (Problems of Tribology, 2014)
In this article is a short presentation concerning abrasion wear on moving parts pressing tools in the area of powdered metallurgy. Moreover is described an allocation choice device to optimize alternative material and a description of this alternative used with material 19 436. Presented also is a principle for a new machinery solution to carry out laboratory tests with varied materials. A description of a mathematically parallel action by simulation of abrasion wearing in presentation mechanism is listed.